EUropean Monetary System : Developments and Perspectives, Occ. Paper No. 73. (Occasional Papers; Occasional Paper, 1990)
This paper discusses various developments and perspectives of the European Monetary System (EMS). There have been three phases in the development of the EMS: from its beginning in March 1979 to March 1983, can be seen as a phase of trial and orientation; from March 1983 to 1987, can be described as one of consolidation; and The Basle/Nyborg agreement marked the end of the consolidation phase, characterized by the striving for stability, the emergence of the deutsche mark as the anchor currency, and the predominance of intramarginal intervention in partner currencies. EMS has allowed simultaneous progress toward external and internal stability. The EMS Agreement provided for fluctuation margins offering some flexibility and for the possibility of central rate changes, which could compensate for diverging monetary policies. As divergences were narrowed, central rate adjustments could be small so as not to affect market rates; thus minimizing the potential for destabilizing capital flows.